A comparative analysis of sustainability of the usual food intakes of the Iranian population, Iranian food-based dietary guidelines, and optimized dietary models - Sobhani, Seyyed Reza; Edalati, Sareh; Eini-Zinab, Hassan; Kennedy, Gina; Omidvar, Nasrin (Frontiers in Sustainable Food Systems, 2022)
Promoting sustainable diets might contribute toward achieving sustainable development goals. Considering the importance of national food-based dietary guidelines (FBDGs), this study aimed to assess and compare the sustainability dimensions of the usual Iranian dietary intakes with sustainable optimal diets based on Iranian (2006 and 2015 versions), Mediterranean, and vegetarian FBDGs. The usual dietary intakes of Iranian households were estimated using household expenditure survey data. Diet sustainability, including environmental (water, carbon, and land) footprints, cost, and nutrient-rich food (NRF) index, was calculated for the usual diet and compared with those of different FBDGs. Using linear and goal programming, optimal food models were calculated by minimizing environmental footprints and cost and maximizing NRF simultaneously for each FBDG, while maintaining nutritional considerations recommended by the FBDGs. Replacing the usual dietary intake of Iranians with the optimal diet based on the 2016 Iranian FBDG was associated with reductions equal to 20.9% for water footprint, 22.48% for carbon footprint, 20.39% for land footprint, 31.83% for cost, and 7.64% increase in NRF index. The optimal model based on the 2016 Iran FBDG was 10% more sustainable compared with the 2005 version. Changing the usual consumption of Iranians to the optimal model based on the Mediterranean pyramid was accompanied by the highest NRF index, lower environmental footprints, and cost compared to other models. The recent Iranian FBDG, compared with the older one, was more sustainable. Considering the dimensions of a sustainable diet for future FBDG revisions is recommended.